Influence of Membrane Thickness on Membrane Degradation and Platinum Agglomeration under Long-term Open Circuit Voltage Conditions. (20th January 2015) - Zhao, Ming; Shi, Weiyu; Wu, Bingbing; Liu, Wenming; Liu, Jianguo; Xing, Danmin; Yao, Yingfang; Hou, Zhongjun; Ming, Pingwen; Zou, Zhigang
Graphical abstract: Highlights: The degradation of three composite membranes with various thicknesses under OCV was investigated. A high hydrogen crossover would accelerate the thinning of the composite membranes. Pt particle growth can be enhanced due to the hot point generated by permeable hydrogen and oxygen. Abstract: Membrane chemical degradation and platinum catalyst agglomeration under long-term open circuit voltage (OCV) conditions were investigated using three types of composite membranes with various membrane thicknesses. Hydrogen permeation increases as membrane thickness decreases, which has a significant influence on proton exchange membrane and platinum catalysts. Higher Hydrogen permeation accelerated the membrane degradation, resulting in the thinning of membrane which can be verified by fluoride emission rates (FERs). Carbon-supported platinum catalysts also experienced agglomeration under OCV conditions. The statistics of platinum size distribution demonstrated catalysts size growth, ranging from 3.83 to 6.02 nm in diameter along with the increasing hydrogen crossover